Apical transverse motion is associated with speckle-tracking radial dyssynchrony in patients with non-ischemic dilated cardiomyopathy - TİGEN, MUSTAFA KÜRŞAT (TURKISH SOC CARDIOLOGY, 2015)
Objective: Apical transverse motion (ATM) is a new parameter for assessing left ventricular (LV) dyssynchrony. Speckle-tracking radial strain analysis seems to be the best method to identify potential responders to cardiac resynchronization therapy. The aim of our study was to investigate the association between ATM and radial dyssynchrony assessed by speckle-tracking echocardiography in patients with non-ischemic dilated cardiomyopathy (NDC). Methods: We examined 35 NDC patients (mean age 49.2 +/- 28.1 years; 21 males). Cardiac dimension and ejection fraction (EF) were measured. Speckle-tracking analysis was performed on two-dimensional greyscale images in the mid-LV short axis view and apical views to calculate global radial, circumferential, and longitudinal strain (GRS, GCS, GLS), as well as rotational indexes (LV twist and torsion). Radial dyssynchrony was defined as a difference in time to peak systolic radial strain between the anteroseptal and posterior segments with a cut-off value of 130 ms. ATM was estimated using motion traces of 2 opposite apical segments. Results: Radial dyssynchrony was significantly correlated with ATMloop (r=0.78, p<0.001), ATM4CV (r=0.71, p=0.001), ATM3CV (r=0.67, p=0.003), GRS (r=-0.51, p=0.04), GCS (r=-0.55, p=0.03), LV twist (r=-0.58, p=0.02), and LV torsion (r=-0.56, p=0.03). The receiver operating characteristics analysis for ATMloop to distinguish between patients with and without radial dyssynchrony revealed an area under the curve value of 0.88 (CI: 0.73-1.04, p=0.005). The best cut-off value was 2.5 mm for ATMloop (85% sensitivity and 86% specificity). Conclusion: Apical transverse motion is closely associated with radial dyssynchrony assessed by speckle-tracking echocardiography. Quantitative measure of apical rocking has the potential for clinical applications.
Keywords: speckle tracking; tissue Doppler; dyssynchrony; CARDIAC RESYNCHRONIZATION THERAPY; VENTRICULAR ROTATIONAL MECHANICS; INTEGRATIVE APPROACH; EUROPEAN-SOCIETY; STRAIN; ECHOCARDIOGRAPHY; GUIDELINES; CARDIOLOGY